Morphology and linear rheology of comb-like copolymer melts with high grafting density: Ⅱ. Heterografted PVSt-g-(PS/PE) comb-like copolymer with short backbone and mixed side chains - Lin, Yichao (2020)
A series of heterografted PVSt-g-(PS/PE) based on polystyrene (PS) backbone with mixed PS and polyethylene (PE) side chains was obtained, in which the branching density of PVSt-g-(PS/PE) was above 72%. Because of the extremely short backbone, long side chains and high branching density in these comb-like copolymers, the topological structure of PVSt-g-(PS/PE) was similar to asymmetrical star copolymers. By adjusting the molar ratio of PS and PE side chains, the total PS (PVSt backbone + side chain PS) volume fraction in the graft copolymers could be adjusted. PVSt-g-(PS/PE) showed a microphase-separated structure at the melt state, depending on the composition of the copolymers. When the volume fraction of PS changed from 42.7% to 76.9%, the microphase-separated structures changed from lamellar phase structure to cylindrical morphology. Furthermore, all the PVSt-g-(PS/PE) samples with the microphase-separated structure showed a typical rheological behavior of cross-linked network-like structure, but the change trend of melt elasticity of the copolymer with increasing temperature depended on the microphase-separated structure.